Computational Analysis of Temperature Effects on Monocrystalline PV Module using MATLAB - Qasir Ali Memon; Abdul Majeed Shaikh; Shoaib Ahmed Shaikh; Muhammad Fawad Shaikh; Shakil Ahmed Jiskani (Sir Syed University Research Journal of Engineering and Technology, 2022)
The world has moved from fossil fuels to renewable energy resources due to adverse environmental impacts, limited sources, and economic issues. It is not necessary that renewable energy sources have always led to many advantages but have drawbacks like weather dependency, unreliability, storage problems, and upfront costs. This study focuses on one of the major types of RES solar PV systems. The data is used from the specification of solar modules at Sukkur IBA University Sindh Pakistan. Solar photovoltaic output depends upon the weather conditions which vary from time to time resulting in variation in irradiance, temperature, power, and efficiency. This paper aims to observe the effects of the temperature ranging from 1 to 55°c on the efficiency of the monocrystalline photovoltaic module using MATLAB/Simulink. The performance parameters could be Open Circuit Voltage (VOC), Short Circuit Current (ISC), Maximum Power Point Current (IMP), Maximum Power Point Voltages (VMP), Fill Factor (FF), and Efficiency (η). Results from the simulation show that the estimated variation of silicon solar cell parameters such as VOC, IMP, series resistance, FF, and η decrease frequently with increasing temperature. And some parameters such as ISC, IMP, and temperature of the panel increase with rising ambient temperature.World has moved from fossil fuels to renewable energy resources due to adverse environmental impacts, limited sources, and economic issues. It is not necessary that renewable energy sources have always led to many advantages but have drawbacks like weather dependency, unreliability, storage problems and upfront costs. This study focusses on the one of the major types of RES solar PV system. The data is used from the specification of solar modules at Sukkur IBA University Sindh Pakistan. Solar Photovoltaic output depends upon the weather conditions which varies time to time resulting variation in irradiance, temperature, power, and efficiency. This paper aims to observe the effects of the temperature ranging 1 to 55°c on the efficiency of the mono-crystalline photovoltaic module using MATLAB/Simulink. The performance parameters could be as open circuit voltage (VOC), short circuit current (ISC), maximum power point current (IMP), maximum power point voltages (VMP), Fill Factor (FF) and efficiency (η). Results from simulation shows that the estimated variation of silicon solar cells parameters such as open circuit voltages, maximum power point voltages, series resistance, fill factor and efficiency decrease frequently with increasing temperature. And some parameters such as short-circuit current, maximum power point current and temperature of the panel increases with rising ambient temperature.